Eksplorasi Remediasi Miskonsepsi Fisika: Sebuah Tinjauan Literatur Sistematis - Putu Nita Kusuma; Redhana, I Wayan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
Misconceptions in Physics are very risky for learning, so a deep understanding of intervention to overcome Physics misconception is necessary. In order to accommodate this purpose, a review of physics misconception remediation efforts is important to do. So far, reviews on remediation of Physics misconceptions are still limited. This research aims to describe: 1) the trend of Physics misconception remediation research in terms of publication year, research objectives, research approaches, and research subjects, 2) Physics concepts that were given remediation treatment, 3) the effectiveness of Physics misconception remediation efforts in reducing misconceptions. The research method used was a Systematic Literature Review (SLR) of the literature from 2019-early 2025 on the Scopus, ERIC, and Google Scholar databases. The results showed that the trend of misconception remediation research was conducted mostly in 2023 with the subject of high school students. The order of Physics misconception remediation efforts from the most widely applied consecutively is by applying learning media (interactive media, worksheet, and e-module), learning models (CCM, inquiry, SSCS, synectis model), learning methods (narrative feedback, refutation text), learning strategies (cognitive conflict and generative), and learning approaches (multiple representation). These results can contribute to improving the quality of Physics learning, especially providing a variety of options for educators and researchers to designing intervention to correct Physics misconceptions.